A cidade “na palma da mão”: experiências de mulheres em situação de rua em São Paulo - Maria Vany de Oliveira (Storia delle Donne)
Issues related to people experiencing homelessness in Brazilian cities have been the main target of my academic attention for quite a long time. An exploration of the components of such social group drove e me to undergo extensive research in the city of São Paulo in the period between 1970 and 2005. The very existence of homelessness is one of the manifestations of the actual relationships in contemporary society. Therefore, when dealing with people struggling with homelessness, we must consider the social situations that create the structures a social group belongs to. This homeless group includes a contingent of women, with an exquisite diversity in their perceptions of life, experiences and stories. Women who are surviving homelessness in the city of São Paulo are in fact the main focus of this article. In particular, the life trajectories of three homeless women are observed with the purpose to enhance the comprehension of the reasons why they started to live on the streets, and analyze their perceptions of the urban space. In the course of my research, I adopted methodological procedures typical of oral history, together with a methodology which supports the participation of the subjects of study, and the collective construction of knowledge.